Respostas fisiológicas e metabólicas em juvenis de Tambaquis (Colossoma macropomum) expostos a situações de estresse: hipóxia e exposição ao ar - Luanna do Carmo Neves (2021)
The objective of this study was to evaluate the physiological and metabolic responses in juveniles of Colossoma macropomum submitted to stress of hypoxia and exposure to air. In experiment 1, animals were subjected to the treatments of normoxia (6.27 ± 0.42 mg L-1) and hypoxia (0.92 ± 0.37 mg L-1) for three days, after which all animals were kept in normoxia for four days. Blood samples were collected 24 and 72 hours after the onset of hypoxia and 24, 48 and 96 hours after the reestablishment of normoxia. In experiment 2 the animals were subjected to tests of exposure to air for 30 and 60 minutes, blood samples were collected immediately after exposure, one, 24 and 48 hours after exposure. Both experiments did not show mortality. In experiment 1: The highest glucose level was recorded after 24 h (P <0.05); the highest lactate level was at 72 recovery; and the highest blood pH was at 24 and 72 h (P <0.05). The highest concentration of PvCO2 was after 24 (P <0.05), while at 96 of recovery it was equivalent to basal (P> 0.05). The PvO2 variable was only greater than the basal at 24 h of recovery (P <0.05). In experiment 2: glucose, there was an interaction between the exposure time and different collection times with higher values for the exposure of 60 min compared to the exposure of 30 min in the collection of 1 hour, while after 24 hours the levels did not differ from basal. Another variable that had an interaction was lactate with higher values for exposure immediately and one hour after exposure. Blood pH varied between collections, with a lower value after 1 h in animals exposed for 60 min. For PvCO2 and PvO2 there was an interaction between the exposure times and the collection times, they were inversely proportional in the collection after 1h. HCO3- values differed between exposure times and varied between collections. C. macropomum was able to recover the main stress indicators (glucose and lactate) with in the 48 hours after the different types of stress, thus restoring its homeostasis.